Current state and prospects of implementation of data standardization in the health care system of Ukraine (literature review) - D.Ye. Kaduk; T.M. Aleksandrova; P.S. Talapova; I.B. Agieieva; M.M. Ved; M.O. Trofymenko; M.R. Kolesnyk; T.S. Nesmiian (Medičnì Perspektivi)
The orientation of the world medical community, and Ukraine in particular, towards the improvement of the quality of medical services includes the introduction of modern tools and methods for quality regulation in the healthcare system. The focus of research on the modernization of medical services, methods and forms of treatment and diagnosis, as well as focus on global experience in regulating the quality of services provided by relevant institutions, undoubtedly contributes to the transition of the Ukrainian healthcare system to a new level. One of the most powerful and modern ways to improve the medical health care system is to introduce the standardization of the format and content of medical data. Quality implementation of the standardization program is a leading factor in the improvement of the quality of medical services, such as: early detection of diseases and emergencies, setting new therapeutic goals, improving the quality of clinical trials, improving of assessment of the quality of medical services and work of the doctors and nursing staff, improving the efficiency of health care programs, improving the safety of use of medical devices, forecasting medical consequences, reducing administrative costs, integrating artificial intelligence into the healthcare system, etc.